2022
DOI: 10.1177/01454455221130002
|View full text |Cite
|
Sign up to set email alerts
|

Slope Identification and Decision Making: A Comparison of Linear and Ratio Graphs

Abstract: Applied behavior analysts have traditionally relied on visual analysis of graphic data displays to determine the extent of functional relations between variables and guide treatment implementation. The present study assessed the influence of graph type on behavior analysts’ ( n = 51) ratings of trend magnitude, treatment decisions based on changes in trend, and their confidence in decision making. Participants examined simulated data presented on linear graphs featuring equal-interval scales as well as graphs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Visualization of Large Value Ranges A common way to display time-series with order of magnitude variations is to use a line graph with logarithmic scaling [32,38,40]. However, most of the previous research on large value ranges has been done for time-independent data.…”
Section: Visualization Of Time-seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Visualization of Large Value Ranges A common way to display time-series with order of magnitude variations is to use a line graph with logarithmic scaling [32,38,40]. However, most of the previous research on large value ranges has been done for time-independent data.…”
Section: Visualization Of Time-seriesmentioning
confidence: 99%
“…The "default" way to visualize large value ranges, is to use a logarithmic scale. However, reading values from a logarithmic scale is not intuitive [32]. This is evidenced by the focus of previous techniques for large value ranges on perceptually linear scaling for both the mantissa 𝑚 and the exponent 𝑒 of a value 𝑣 = 𝑚 • 10 𝑒 [9,26,27].…”
Section: Visualization Designsmentioning
confidence: 99%
“…Clear, replicated patterns across phases in SCDs reveal intervention effects, with stability in responses across consistent conditions indicating a functional relation between variables. Establishing this functional relation requires evaluating data traits like level, trend, and response immediacy (Kubina et al, 2023), which SCD researchers have suggested group design-related statistical analysis overlook (e.g., Maggin et al, 2022; Wolery et al, 2010). Nonetheless, the push for quantitative alternatives grows due to the limitations of visual analysis.…”
mentioning
confidence: 99%
“…Nonetheless, the push for quantitative alternatives grows due to the limitations of visual analysis. Critics note that visual analysis does not provide a practical, universal metric of treatment magnitude (Browder et al, 1989; Riley-Tillman et al, 2020) and is applied inconsistently by observers (Kubina et al, 2023; Ninci et al, 2015).…”
mentioning
confidence: 99%